ANALISIS PENGHINDARAN PAJAK DENGAN PENDEKATAN FINANCIAL DISTRESS DAN PROFITABILITAS - Indra Iman Sumantri; Donny Indradi (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2020)
This study aims to analyze tax avoidance with a financial distress approach and profitability approach in consumer goods industry sector companies listed on the IDX in 2013-2017. This research uses quantitative research methods with secondary data obtained through intermediate media that has been processed and has been documented. The population in this study were forty-four companies after being selected using purposive sampling into as many as fourteen companies with five years of research so that the total sample was 70. This study used a hypothesis testing tool, namely multiple linear regression test, partial test (t test), the coefficient of determination, the correlation coefficient test, with a significance level of 5%. The result of this research is that financial distress has a negative and significant effect on tax avoidance. Profitability has no effect on tax avoidance. Keywords : Financial Distress, Profitabilitas, Tax Avoidance